PROBLEMS OF A METHODOLOGICAL APPROACH CONCERNING THE DEVELOPMENT OF LEASING IN RAILWAY TRANSPORT - Pozdnyakova, L. A.; Zhuravleva, Ye. N. (Science and Transport Progress, 2006)
The article examines practicability of use of leasing operations on the railway transport in the conditions of market economy, singles out the problematic issues and economic advantages of leasing agreements, substantiates the expediency of use of leasing mechanisms as is proved by experience of Russian railways.